LAJU ANGKUTAN SEDIMEN MELAYANG DI SUNGAI WIMBI SUB DAS WIMBI KABUPATEN POSO - Herman Harijanto; Abdul Wahid; Arief Sudhartono; Nikteri Perori (Lambung Mangkurat University-Indonesia, 2021)
The research purpose was to determine of floating sediment loading rate which transported along Wimbi river water runoff and analyzed the relationship between water discharge with floating sediment discharge in the Wimbi river. The method used in this study was a survey method, namely by conducting direct measurements in the field, including: measurement of water discharge and water sampling for analysis of floating sediment content. Parameter measured for the purpose of analyzing the sediment loading rate, namely floating sediment concentration Cs (mg / l), river water discharge Q (m3 / sec) and floating sediment discharge Qs (kg / sec). The relationship between water discharge and sediment discharge was analyzed using a suspended sediment rating curve. The results showed the flow of river water flowing at the cross section of the Wimbi river ranged from 0.88 m3 / sec - 13.7 m3 / sec (average of 6.17 m3 / sec). Furthermore, the height of the water level (H) flowing in the cross section of the Wimbi river ranged from 0.5 to 1.84 m with average = 1.14m. Sediment loading rates float in the Wimbi river ranged from 2.110 - 99.511kg / sec (average of 35.222 kg / sec). The analyzed results of the relationship between water discharge and floating sediment discharge obtained a positive relationship with a correlation value of 0.96.